Blockchain Technology in Financial Management: A Case Study of Digital Transformation in Banking - Zidnal Falah; Abdul Robi Padri; Feri Hardiyanto (Politeknik Siber Cerdika Internasional, 2025)
Blockchain technology, known for its decentralized and transparent transaction recording system, is increasingly attracting attention in the banking sector, especially in financial management. In Indonesia, despite the many potentials offered by blockchain, its adoption in the banking sector still faces various challenges related to regulation, technology readiness, and human resource training. Therefore, it is important to explore the potential and barriers to blockchain adoption in this sector. This study aims to analyze the application of blockchain technology in banking financial management, identify its challenges and benefits, and evaluate the readiness of banks in Indonesia to adopt the technology. This type of research is qualitative research with a case study design. Data were obtained through in-depth interviews with bank management, licensed employees, and customers, as well as analysis of relevant documents. The data analysis technique used a thematic analysis approach to explore in-depth information about blockchain implementation. The research findings show that blockchain can improve transparency, cost efficiency, and transaction security in banking. However, the biggest challenges faced are unclear regulations, difficulty integrating the technology with existing banking systems, and limited employee training in some small banks. Blockchain has great potential to modernize financial management in the banking sector, but its implementation requires clear policies, adequate training for employees, and efforts to improve customer understanding. This research provides insights for banks and policymakers to design effective strategies for adopting blockchain technology, and provides recommendations to improve the readiness of human resources and technological infrastructure in the banking sector.